Cervical alignment following laminoplasty for cervical spondylotic myelopathy - Sharma, Ravi (Surg Neurol Int, 2019)
BACKGROUND: Laminoplasty can result in the loss of cervical lordosis (LOCL) or the development of kyphosis after surgery. Here, we evaluated the clinical and radiological parameters involved in predicting the postoperative LOCL following laminoplasty in patients with cervical spondylotic myelopathy (CSM) and ossification of the posterior longitudinal ligament (OPLL). METHODS: For 50 patients with CSM and 35 with OPLL undergoing laminoplasty, preoperative and 1-year postoperative X-rays were obtained to determine the incidence and risk factors contributing to postoperative LOCL. The patients were divided into two groups depending on whether the preoperative T1 slope was above or below the median preoperative T1S (26°); Group A – high T1 slope group (n = 40) and Group B – low T1 slope group (n = 45). RESULTS: Following laminoplasty, Group A patients had significantly higher preoperative lordosis (C2-C7 Cobb’s angle) (P = 0.001) and significantly higher LOCL (P = 0.02) versus Group B patients with low T1 slopes. The preoperative T1 slope was also found to be significantly correlated with the preoperative C2-C7 Cobb’s angles (R = 0.619, P = 0.001), LOCL (R = 0.487, P = 0.001), and preoperative C2-C7 sagittal vertical axis (R = 0.480, P = 0.001). Utilizing multivariate analysis and a generalized linear model, the preoperative T1 slope significantly impacted the Oswestry disability index (ODI) index (P = 0.002) and frequency of LOCL (P = 0.001) following laminoplasty. CONCLUSION: The preoperative T1 slope is a significant predictor of the LOCL and change in ODI following laminoplasty for CSM/OPLL utilizing a cutoff value of 29.5°.